NYERI DAN LAMA PERSALINAN KALA IDI PUSKESMAS BANJARNEGARA 1 KABUPATEN BANJARNEGARA - Dewie Sulistyorini; Wahyu Rofingah (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2021)
World Health Organization (WHO) estimated 800 women die d every day due to pregnancy complications and the birth process. About 80% of deaths maternal is the result of increased complications during pregnancy, childbirth and breath. Maternal Mortality Rate (MMR) in the world which is 289,000 inhabitants. Almost two thirds Maternal death is caused by direct i.e. bleeding (25%), infection/ sepsis (15%), eclampsia (12%), abortion unsafe (13%), obstructed labor (8%), and other direct causes such as pregnancy ectopic, embolism, and other things related to anesthesia problems (8%), other causes (19%). A preliminary study was conducted at the Banjarnegara 1 Health Center regarding labor pain in the active phase of the 1st stage and it was found that 67% of mothers stated moderate pain and 33% said severe pain. The purpose of this study was to determine the relationship between pain and duration of labor first stage at the Banjarnegara 1 Public Health Center, Banjarnegara Regency. Analytical descriptive research design with a cross sectional approach. The research population was mothers who gave birth at the Banjarnegara Health Center 1. The sampling technique was using a purposive sampling technique as many as 35 respondents. All samples will be given a questionnaire about pain and the duration of labor is calculated using hours. The results showed that more than half the level of labor pain in the first stage of the respondents were in the moderate category, namely 18 respondents (52%), most of the duration of labor in the first stage of the respondents were included in the normal category, namely as many as 24 respondents (68%) and there was a relationship between pain and first stage of labor with p_value 0.018. Things that can be done by health workers to reduce labor pain and duration of labor is to bring birth attendants and be taught deep breathing techniques in addition to reducing anxiety.